Spatiotemporal Characteristics of NPP Changes in Frozen Ground Areas of the Three-River Headwaters Region, China: A Regional Modeling Perspective - Hu, Jianan; Nan, Zhuotong; Ji, Hailong (Frontiers in Earth Science, 2022)
Permafrost degradation triggered by climate warming can disturb alpine ecosystem stability and further influence net primary productivity (NPP). Known as the “water tower of China”, the Three-River Headwaters Region (TRHR) on the eastern Qinghai-Tibet plateau (QTP), is characterized by a fragile alpine meadow ecosystem underlain by large areas of unstable permafrost and has been subject to rapid climate change in recent decades. Despite some site-specific studies, the spatial and temporal changes in NPP in the different frozen ground zones across the TRHR associated with climate change remain poorly understood. In this study, a physically explicit Noah land surface model with multi-parameterization options (Noah-MP) was employed to simulate NPP changes on the TRHR during 1989-2018. The simulation was performed with a spatial resolution of 0.1° and a temporal resolution of 3hr and validated at two sites with meteorological and flux observations. The results show that the average NPP was estimated to be 299.7 g C m-2 yr-1 in the seasonally frozen ground (SFG) zone and 198.5 g C m-2 yr-1 in the permafrost zone. NPP in the TRHR increased at a rate of 1.09 g C m-2 yr-2 during 1989-2018, increasing in 1989-2003 and then decreasing in subsequent years. The NPP in permafrost area increased at a rate of 1.43 g C m-2 yr-2 during 1989-2018, which is much higher than the rate of change in NPP in the SFG area (0.67g C m-2 yr-2). Permafrost degradation has complicated ecosystem implications. In areas where permafrost degradation has occurred, both increasing and decreasing changes in NPP have been observed.